PENGARUH KOREAN WAVE DAN BRAND AMBASSADOR TERHADAP MINAT BELI ONLINE PADA MARKETPLACE TOKOPEDIA - Devitasari, Ginda Aprilia; Fitrianatsany, Fitrianatsany (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2024)
The purpose of this research is to identify how Korean Wave and brand ambassadors effect online purchasing intention in the Tokopedia marketplace. The research method used is quantitative using multiple regression analysis. This research uses primary data obtained from distributing questionnaires to Tokopedia marketplace users who are the population in this study. Users aged 17-50 years and who have used the Tokopedia marketplace for the last two years and made purchases at least 4 times are the sample. This research uses a non-probability sampling technique with a proportional sampling type with a sample of 100 respondents. Based on the test results for the Korean Wave and Brand Ambassador variables, they have a positive and significant effect on Online purchasing intention on the Tokopedia Marketplace. The results of the F test simultaneously with the Korean Wave and Brand Ambassador variables have a significant effect on online purchasibg intention, with it being known that Fcount is 10.643 > F table 2.358 and is significant 0.000 < 0.1. Meanwhile, partially the Korean wave variable has a positive and significant effect on online purchasing intention, and the brand ambassador variable has a positive and significant effect on online purchasing intention. The R Square coefficient of determination test is 0.380, meaning that the percentage contribution of the Korean Wave and Brand Ambassador variables to online purchasing intention is 38% and the remaining 62% comes from other variables outside the research.